2017
DOI: 10.1051/epjconf/201714015004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the representativeness of durability tests for wood pellets by DEM Simulation – Comparing conditions in a durability test with transfer chutes

Abstract: Abstract. Dust generation when handling wood pellets is related to the durability of the product, in other words the wear rate of particles subject to forces. During transport, storage and handling wood pellets undergo different forces when interacting with different pieces of equipment. This paper assesses the representativeness of the tumbling can test in relation to transfer chutes, by comparing forces acting on wood pellets in durability tests and in transfer chutes using DEM. The study also incorporates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…The order of magnitude of the bond elasticity modulus (10 7 -10 8 Pa) and the corresponding range of the normal stiffness coefficient of the bond (10 10 -10 11 N m −3 ) applied in our study were similar to the values of the bond elasticity and stiffness applied in the DEM modelling of loading of pinewood chip briquettes by Xia et al [38], the durability of wood pellets found by Mahajan et al [39], and the breakage of biomass pellets studied by Gilvari et al [40]. The maximum bond tensile strength σ c of 36 MPa applied in our study for oak (MC = 8% and σ z = 120 MPa) corresponded to that applied by Gilvari et al [40] (σ c = 35 MPa) and Mahajan et al [39] (σ c = 40 MPa) to model pellet behaviour. The~30% decrease in the bond strength with an increase in MC from 8% to 20% was consistent with the results of Whittaker and Shield [2] and Li and Liu [9], who indicated that an excessively high MC reduces the binding forces between particles.…”
Section: Simulation Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The order of magnitude of the bond elasticity modulus (10 7 -10 8 Pa) and the corresponding range of the normal stiffness coefficient of the bond (10 10 -10 11 N m −3 ) applied in our study were similar to the values of the bond elasticity and stiffness applied in the DEM modelling of loading of pinewood chip briquettes by Xia et al [38], the durability of wood pellets found by Mahajan et al [39], and the breakage of biomass pellets studied by Gilvari et al [40]. The maximum bond tensile strength σ c of 36 MPa applied in our study for oak (MC = 8% and σ z = 120 MPa) corresponded to that applied by Gilvari et al [40] (σ c = 35 MPa) and Mahajan et al [39] (σ c = 40 MPa) to model pellet behaviour. The~30% decrease in the bond strength with an increase in MC from 8% to 20% was consistent with the results of Whittaker and Shield [2] and Li and Liu [9], who indicated that an excessively high MC reduces the binding forces between particles.…”
Section: Simulation Resultssupporting
confidence: 89%
“…The approximately twofold decrease in the bond elasticity modulus with an increase in MC from 8% to 20% applied in our simulations fitted very well to the rate of decrease in pellet elasticity determined experimentally by Gallego et al [51]. The order of magnitude of the bond elasticity modulus (10 7 -10 8 Pa) and the corresponding range of the normal stiffness coefficient of the bond (10 10 -10 11 N m −3 ) applied in our study were similar to the values of the bond elasticity and stiffness applied in the DEM modelling of loading of pinewood chip briquettes by Xia et al [38], the durability of wood pellets found by Mahajan et al [39], and the breakage of biomass pellets studied by Gilvari et al [40]. The maximum bond tensile strength σ c of 36 MPa applied in our study for oak (MC = 8% and σ z = 120 MPa) corresponded to that applied by Gilvari et al [40] (σ c = 35 MPa) and Mahajan et al [39] (σ c = 40 MPa) to model pellet behaviour.…”
Section: Simulation Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The discrete element method (DEM) which was introduced by Cundall and Strack (1979) was extended with the parallel bonded particle model (BPM) of Potyondy and Cundall (2004) which appears to be very useful in providing a particle scale insight into the bonding mechanisms. DEM simulations reproduced the results of the experimental tests of the pressure compaction of biomass very well (Ilic et al, 2018), in terms of the mechanical behaviour of pinewood chips in cyclic loading (Xia et al, 2019), durability (Mahajan et al, 2017), and the breakage strength of wood (Horabik et al, 2021) and biomass pellets (Gilvari et al, 2020). DEM modelling of the mechanical behaviour of compacted biomass requires further study in order to verify its applicability to different types of biomass and experimental conditions.…”
Section: Introductionmentioning
confidence: 86%